Do all geckos hatch in the same way? Histological and 3D studies of egg tooth morphogenesis in the geckos Eublepharis macularius Blyth 1854 and Lepidodactylus lugubris Duméril & Bibron 1836. (17th August 2020) - Hermyt, Mateusz; Metscher, Brian; Rupik, Weronika
Abstract: The egg tooth of squamates evolved to facilitate hatching from mineralized eggshells. Squamate reptiles can assist their hatching with a single unpaired egg tooth (unidentates) or double egg teeth (geckos and dibamids). Egg tooth ontogeny in two gekkotan species, the leopard gecko Eublepharis macularius and the mourning gecko Lepidodactylus lugubris, was compared using microtomography, scanning electron microscopy, and light microscopy. Investigated species are characterized by different hardnesses of their eggshells. Leopard geckos eggs have a relatively soft and flexible parchment (leathery) shell, while eggshells of mourning geckos are hard and rigid. Embryos of both species, like other Gekkota, have double egg teeth, but the morphology of these structures differs between the investigated species. These differences in shape, localization, and spatial orientation were present from the earliest stages of embryonic development. In mourning gecko, anlagen of differentiating egg teeth change their position on the palate during embryonic development. Initially they are separated by condensed mesenchyme, but later in development, their enamel organs are connected. In leopard geckos, the localization of egg tooth germs does not change, but their spatial orientation does. Egg teeth of this species shift from inward to outward orientation. This is likely related to differences in structure and mechanical properties of eggshells in the studied species. In investigated species, two hatching mechanisms are possible during emergence of young individuals. We speculate that mourning geckos break the eggshell through puncturing action with egg teeth, similar to the pipping phase of chick and turtles embryos. Egg teeth of leopard geckos cut egg membranes similarly to most squamates. Our results also revealed differences in egg tooth implantation between Gekkota and Unidentata: gekkotan egg teeth are subthecodont (in shallow sockets), while those in unidentates are acrodont (attached to the top of the alveolar ridge). © 2020 Wiley Periodicals LLC Abstract : The evolution of egg teeth in squamates was closely connected with the transition from aquatic to fully terrestrial reproduction. Squamate reptiles can assist their hatching with a single unpaired egg tooth (unidentates) or double egg teeth (geckos and dibamids). Embryos of leopard gecko and mourning gecko, as in other Gekkota, have double egg teeth, but the morphology of these structures differs between the investigated species. These differences in shape, localization, and spatial orientation were present from the earliest stages of embryonic development.